The evaluation of land use cover changes through the composite approach of Landsat 8 and the land use capability index for the Bedadung watershed - Basuki Basuki; Bambang Hermiyanto; Subhan Arif Budiman; Fariz Kustiawan Alfarisy (Brawijaya University, 2023)
Land use changes become a problem that contributes to the decline in the watershed function and performance. Bedadung watershed divides Jember Regency, which has upstream from Mount Raung and a downstream Indonesian Ocean. During the last ten years in Jember, there has been a flood from the overflow of the Bedadung river, which is unable to accommodate water from upstream. It is alleged that the cause of flooding in upstream of the Bedadung watershed is land cover and land capability that has changed. The purpose of this study was to assess land use changes using a composite approach to Landsat 8 imagery and land capability index for the upstream of the Bedadung watershed. The results showed that land cover of the Kesambi sub-watershed during 1995-2020, forest decreased by 34.74%, settlements and open land decreased by 47.25%, dry land increased by 120%, while plantations and rainfed rice fields were fixed. The decrease in forest area can disrupt the water cycle, thereby increasing runoff volume and water discharge, causing flooding downstream of the Bedadung watershed and upstream of the Bedadung watershed. Land capability evaluation of the upstream of Kesambi sub-watershed, area of Bedadung watershed was mostly in class III, covering 5782.9 hectares (85.53%), class IV covering 214.8 hectares (3.18%), class VI covering 379.7 hectares (5.62%), and class VII covering 383.9 hectares (5.68%) with limiting factors of effective soil depth, land slope/slope, erosion sensitivity, and drainage. Areas with class III land capability covering land mapping units 1, 2, 3, 6, and 7 can be utilized as agricultural with good conservation technology, while land mapping units 4.5, and 8 are only capable for forest areas.